Desain Sistem Pencacah Brondol Sawit dengan Variasi Ketebalan Spacer Cutter Produk 3D FDM - adhe anggry; Indra Feriadi (Manutech : Jurnal Teknologi Manufaktur, 2022)
The increase in ????oil palm plantations has an impact on increasing plantation waste produced, one of which is palm oil and has a positive impact on the development of palm oil waste processing technology. Palm kernel crushing machine as one of the supporting animal feed productions can produce shreds with fiber and cake dimensions that are suitable for animal feed. However, the types of livestock require varying dimensions of fiber and meal chips. The purpose of this research is a more effective completion of the project 'Design and Analysis of Palm Oil Palm Oil Counter System with 3D FDM Product Spacer Cutter Thickness'. The design process of a machine component must consider the stresses and deformations that occur so that it can be known whether the components designed are of good quality or not. The five steps of the problem-solving process are as follows: 1) Define requirements, 2) Gather/analyze information, 3) Develop several options, 4) Select the best option, and 5) Implement the design. Design simulations and analysis were carried out on the components of the chopping shaft, spacer cutter, and compression springs. From the simulation results obtained the design data of the chopping shaft using steel material, dimensions Æ20mm/Æ16mm, and uniform load w= 0.24 N/mm. Analysis of maximum bending stress sB = 1.847 MPa, torsional stress t = = 0.103 MPa, and deflection fmax = 4.201 microm. The design of the spacer cutter component uses ABS material, dimensions Æ70mm/ Æ20mm with a thickness variation of 10-15 mm, and a compressive load of F= 100 N. Analysis of Von Mases Stress is 0.0319665 MPa and maximum displacement is 0.0000713021 mm. The design of the compressed spring components uses carbon steel, the wire dimensions are 2 mm, the inner diameter is 20 mm, and the length is 100 mm. The spring inspection analysis is positive.